The effect of pitch dimensions and players` format on heart load and external load in semi-professional soccer players - Papadopoulos, E. K.; Tsentidou, G.; Metaxas, T. I.; Mandroukas, A.; Michailidis, Y.; Galazoulas, C. A.; Christoulas, K.; Papadopoulos, K.; Papadopoulos, M. (Trends in Sport Sciences, 2023)
Introduction. Soccer players need to acquire high level of technical, tactical, and physical skills to be able to play at professional level. Changing the pitch size (while keeping the same format of play) causes variations in the relative area per player (calculated as the area of the pitch divided by the number of outpitch players involved in the game). This manipulation is one of the main concerns while using small-sided games (SSG), since different relative areas per player for the same format change the players` responses.